Atlantic versus Pacific Agreement in Agri-food Sectors: Does the Winner Take it All? - Anne-Célia Disdier; Charlotte Emlinger; Jean Fouré (Center for Economic Studies and ifo Institute (CESifo), 2015)
Trade liberalization of the agri-food sector is a sensitive topic in both Transatlantic Trade and Investment Partnership (TTIP) and Trans-Pacific Partnership (TPP) discussions. Using a general equilibrium model, we assess the potential impact of these agreements. The US agri-food sectors would gain from both agreements while almost all their partners and third countries would benefit less. However, the two agreements are not competing, since all the contracting parties' defensive and offensive interests are complementary. Finally, the Atlantic trade may be impacted by the inclusion of harmonized standards within the Pacific agreement but not by its extension to additional members.
Keywords: F13; F15; Q17; 330; mega-trade deals; agri-food; CGE model; Transatlantic Trade and Investment Partnership; Trans-Pacific Partnership